Mediаlogy as an Interdisciplinary Metatheory:Structure and Concept of Modeling - Кияниця, Є. (Київський національний університет імені Тараса Шевченка, 2025)
The main objective of this study is to examine the media as a multilevel communication system encompassing technological, cognitive, socio-cultural, and ethical dimensions of its functioning within the context of digital transformation and evolving modes of information exchange. The relevance of the topic lies in the urgent need for a conceptual understanding of how contemporary media have ceased to operate merely as passive channels of data transmission and have become active constructors of cultural matrices, collective consciousness, and behavioural patterns. This shift necessitates the development of a new metatheoretical framework – mediаlogy – capable of offering an integrated approach to the study of a complex reality in which communication processes emerge at the intersection of humanistic, social, and technological factors. The aim of the research is to formulate an interdisciplinary construction of the metatheory of medialogy, one that systematises contemporary media knowledge and substantiates the significance of concepts such as media literacy, ethical responsibility, and cultural norms in the digital age as essential components for fostering informational resilience and reflective media behaviour. The methodological framework includes theoretical analysis to grasp the multifaceted nature of media; an analytical-synthetic approach combined with systems thinking to elaborate an integrative metatheory; and empirical validation through an expert online survey (CAWI method), designed to identify key evaluations and priorities in the contemporary understanding of media as a social institution. The study concludes that medialogy functions as a metatheoretical paradigm ensuring interdisciplinary coherence across research approaches. It enables the synthesis of empirical data, critical interpretation, and philosophical generalisation, thereby offering a holistic model for understanding and designing the media environment as a space of cultural production, ethical engagement, and cognitive orientation. In this context, media literacy, media ethics, and media culture are not isolated domains but interrelated elements in shaping a responsible public sphere–one that resists manipulative practices, strengthens resilience to informational distortion, and cultivates a renewed humanistic sensibility.

Об’єктом дослідження виступає медіа як багаторівнева комунікаційна система, що охоплює технологічні, когнітивні, соціокультурні та етичні виміри своєї дії в умовах цифрової трансформації та зміни інформаційної взаємодії. Актуальність теми полягає в необхідності концептуального осмислення того, як сучасні медіа перестають бути пасивним каналом передавання даних і набувають статусу активного фундатора культурної матриці, колективної свідомості та поведінкових моделей, що визначає потребу в новій метатеоретичній рамці – медіалогії – здатній забезпечити інтегрований підхід до вивчення складної реальності, де комунікаційні процеси постають у взаємодії гуманітарних, соціальних і технологічних чинників. Мета полягає у розробці міждисциплінарної конструкції метатеорії медіалогії, що систематизує сучасне знання про медіа та обґрунтовує значущість таких концептів, як медіаграмотність, етична відповідальність у медіасфері та культурна норма в цифрову епоху, для підвищення інформаційної стійкості та розвитку рефлексивної медіаповедінки. Методи дослідження охоплюють теоретичний аналіз, що дає змогу осмислити природу і багатогранність медіа; аналітико-синтетичний підхід у поєднанні з моделлю системного мислення для формування інтегративної метатеорії; а також емпіричну верифікацію теоретичних положень шляхом онлайн-опитування експертів (метод CAWI), спрямованого на виявлення оцінок і пріоритетів у сучасному баченні медіа як соціального інституту. Головні висновки зводяться до того, що медіалогія функціонує як метатеорія, що забезпечує міждисциплінарну єдність дослідницьких підходів, дозволяє синтезувати емпіричні дані, критичні інтерпретації та філософські узагальнення, а також створює цілісну рамку для осмислення й моделювання медіасередовища як чинника культурного творення, етичної взаємодії та когнітивної навігації в умовах інформаційної складності, де медіаграмотність, медіаетика й медіакультура постають не ізольованими категоріями, а взаємопов’язаними ланками у формуванні відповідальної публічної сфери, що протистоїть маніпулятивним впливам, забезпечуючи стійкість до інформаційних викривлень та формуючи нову гуманістичну чутливість
Медіалогія як міждисциплінарна метатеорія: структура та концепція моделювання
Keywords: mediаlogy; interdisciplinarity; metatheory; modelling; media; communication; digital technologies; society.; медіалогія; міждисциплінарність; метатеорія; моделювання; медіа; комунікація; цифрові технології; суспільство.